PENGARUH KOMPRES LIDAH BUAYA (ALOEVERA) TERHADAP PENURUNAN SUHU TUBUH PADA BALITA DEMAM DI KLINIK PRATAMA MAHDARINA KOTA MEDAN TAHUN 2025 - Natalia, Kristin - (JURNAL ILMIAH DHDT - KEBIDANAN, 2025)
Fever is the body's natural reaction to an inflammatory infection in the body. Fever is one of the common reasons parents take their children to the nearest health facility. The causes of fever in toddlers are changes in the heat center (thermoregulation) as well as infection with a disease that attacks the body system. An alternative that can be done to reduce the body temperature of a toddler with a fever is to use an Aloe Vera Compress. Compress using Aloe vera will be more effective in accelerating the release of heat from the body because it contains saponin compounds. Aloe vera also contains lignin which can penetrate into the skin, and can prevent loss of body fluids from the surface. The lignin content in the gel can protect the skin from dehydration and maintain moisture. Heat absorption can occur because lignin has the property of penetrating 5x faster into pores and cells, so that a decrease in body temperature in children who have fever can occur. The aim of this research was to determine the effect of applying Aloe Vera compresses on reducing body temperature in toddlers with fever at Pratama Mahdarina Clinic, Medan City. The research method used was Quasy Experimental Design with One Group Pretest-posttest Design. The research population of toddlers with fever was 15 people. Samples were taken using Total Sampling with a total sample of 15 toddlers with fever. Independent Variable Aloe Vera Compress dependent variable Decrease in body temperature of toddlers with fever. Research instrument: Thermometer and Observation Sheet. The results of research using the Wilcoxon Test found a P-Value value of 0.001 < 0.05, which means there is an effect of giving Aloe Vera compresses on reducing body temperature in toddlers with fever at the Mahdarina Pratama Clinic, Medan City in 2025